REASSESSING THE GREEN FINANCING–PROFITABILITY NEXUS: EVIDENCE OF REVERSE CAUSALITY IN INDONESIAN ISLAMIC BANKING (2020–2025): MENINJAU KEMBALI KAITAN ANTARA PEMBIAYAAN HIJAU DAN PROFITABILITAS: BUKTI KAUSALITAS BALIK PADA PERBANKAN SYARIAH INDONESIA (2020–2025) - Dzulfikar Maula Al-Farizi; Anugrah Ibra Pramudya; Malik Khoirurrosyid (Universitas Wahid Hasyim Semarang, 2026)
This study examines the dynamic relationships among operational eco-efficiency, emission reduction, the Green Financing Ratio (GFR), and profitability in Indonesian Islamic commercial banks. Motivated by a gap in the green banking literature, which mostly treats internal environmental performance as a byproduct rather than a driver of green financing and relies on static estimation techniques, this study applies a Vector Error Correction Model (VECM) to an annual composite series built from ten purposively sampled Islamic commercial banks operating in Indonesia between 2020 and 2025. Unit root tests show mixed orders of integration: the Green Financing Ratio is stationary only after first differencing, while profitability, emission reduction, and operational eco-efficiency are stationary in levels. Contrary to the hypothesized directions, Granger causality tests find no significant effect of operational eco-efficiency or emission reduction on the Green Financing Ratio, so Hypotheses 1 and 2 are not supported. Instead, the results reveal a significant unidirectional causality running from profitability to the Green Financing Ratio, and the cointegrating equation confirms a statistically significant positive long-run relationship between the Green Financing Ratio and profitability, giving long-run support to Hypothesis 3. The short-run error-correction estimates further show a significant direct effect of emission reduction on profitability. Forecast Error Variance Decomposition indicates that profitability and the environmental indicators are each largely self-determined, with cross-variable spillovers remaining modest. These findings suggest that, in this sample, internal financial strength precedes rather than follows the expansion of green financing.